KUALITAS PERMEN JELLY SARI BUAH PEPAYA (Carica papaya L.) DENGAN PENAMBAHAN EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) - Livia Adriana; Franciscus Sinung Pranata; Yuliana Reni Swasti (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Jelly candy is a favorite snack of various ages from children to adults because it has an attractive color, delicious aroma and taste, and a chewy texture. In this study, papaya juice (Carica papaya L.) was used as a base ingredient for making jelly candy because papaya is a fruit that is very easy to find and has a relatively cheap price. In order to improve the quality of the papaya jelly candy, roselle calyx extract (Hibiscus sabdariffa L.) was also added. Roselle calyx has been known to have high antioxidants because they contain anthocyanin pigments. The purpose of this study was to determine the effect of variations in the addition of roselle calyx extract to the papaya jelly candy. The experimental design in this study was a completely randomized design with variations in the addition of roselle calyx extract by 0% (control), 15%, 30%, and 45%. The parameters tested in this study include chemical, physical, microbiological, and organoleptic qualities. The results of the research that have been carried out show the addition of 45% roselle calyx extract can produce the best papaya jelly candy based on water content, total titrated acid, antioxidant activity, total anthocyanin, texture, color, and microbiological tests which include total plate count and numbers of yeast molds. Keywords : jelly candy, papaya juice, roselle calyx extract